Production and operations study on Metro Container Corporation - Chiu, Lirie W.; Lorenzo, Carlo Ryan R.; Monoy, Darlene C. (Diliman, Quezon City College of Engineering, 1999)
This Production and Operations Management study was conducted on Metro Pacific Corporation (MetroCan), a company engaged in the production of tin can packaging for commercial goods. The present system was documented. This includes the forecasting technique being used, planning strategy of the company with regards to meeting demand of customers, and the production process. The study was limited to Assembly I, which is concerned with the production of small cans. (maximum 1 gallon capacity). Analyses were conducted to determine the problem areas of the company and the interrelationships of these problems. The group identified three major problem areas and these are: (1) wrong forecasts; (2) high misprint rejects and; (3) insufficient production capacity of some lines. To answer the major problems of the company, recommendations were generated and cost-and-benefit analyses were performed on each of the alternatives o determine their feasibility, in terms of savings over the long-run operations. The alternatives determined to be feasible are: (1) using the method of exponential smoothing as forecast technique; (2) purchase of a more advanced printing machine and; (3) add and upgrade some machines in the 211, 307 and 401 lines.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Metro Container Corporation; Transportation industry; Production engineering